Antifungal activity of mimosa pudica leaves extract against penicillium sp. / Nurul Artiqah Zupilah - Zupilah, Nurul Artiqah (2018)
Currently, synthetic fungicide was used as a prevention to massive post-harvest lost during handling process. The endless use of synthetic fungicide could harm the health of people and environment due to the chemical component of it. Thus, the present research is conducted to look for natural antifungal that could be obtain from plant extract that contain secondary metabolites. The objective of this study are to analyses phytochemical compound of methanolic Mimosa pudica leaves extract by phytochemical screening and to determine the antifungal activity of Mimosa pudica leaves extract on Penicillium sp. The antifungal activity of Mimosa pudica against Peniciliium sp. at different concentration was tested using agar well diffusion method and phytochemical screening was used to test the present of phytochemical compound of Mimosa pudica leaves. Mimosa pudica shows a series of positive result on qualitative phytochemical test alkaloids, flavonoids, saponins, tannis and reducing sugar. However, the antifungal activity of methanolic extract of Mimosa pudica leaves at four different concentrations which are 250, 500, 750 and 1000 mg/ml was unable to inhibit Penicillium sp. In conclusion, secondary metabolites concentration of Mimosa pudica leaves extract does not show antifungal activity toward Penicillium sp.